Um modelo de interação para a programação de dispositivos por crianças na era da Internet das Coisas - Silva Neto, Benedito Ribeiro da (2018)
The Internet of Things allowed the creation of a set of computer systems embedded in everyday objects such as clothes, toys and home appliances. Some of these systems are not just for use but offer possibilities for customization through programming. However, especially for specific audiences, such as small children (4 to 6 years), this universe of differentiated interactions, in which different intelligent devices with particular specifications coexist, may require greater cognitive effort, making it difficult to use programming functionalities. In this scenario, this work presents an interaction model to guide the provision of programming devices for children. For the construction of this model, specified and represented in the Stamper´s Semiotic Ladder, a state-of-the-art survey was performed on the programming of physical devices by infants in early childhood and a case study using Participatory Design techniques with the participation of children between 4 and 6 years old. A feasibility study conducted with a paper-based prototype indicated that children can control devices from programming environments built following the model.